3D High-dose lattice radiotherapy (LRT) with RapidArc thecnolog. (December 2018) - Maggiulli, E.; Florio, E.T.; Valzano, S.; De Luca, M.C.; Tramacere, F.; Portaluri, M.; Natali, M.
Abstract : Purpose: 3D High-dose LRT is the evolution of spatially fraction- ated GRID radiotherapy (SFGRT) for the treatment of locally advanced disease; it pursuits not only the dose escalation but also the idea of facilitating intra-tumoral bystander effect, thus increas- ing the biological effectiveness of the treatment. Methods: With modern RT it has been possible to reconfigure a 2D grid field into a 3D dose lattice, that resulting in a very high dose of radiation concentrated in small spheres, called vertices, within the tumor volume; a "peak-to-valley effect" between vertices is created leaving peripheral normal tissue minimally exposed. Three patients (pelvic LN disease, axillary desease and KG3 of large bowel wall) were selected to be treated with 3D High-dose LRT according to this prescribe schedule:15 Gy for the first two patients and 12 Gy for the last one in single fraction on lattice vertices within the tumor target and after one week 30 Gy (1rst and 3th patients) and 20 Gy (2nd patient) in 10 fractions on the large tumor mass.The lattice plans are generated using RapidArc thecnology (Varian Medical System, Inc.) with Eclipse TPS (AAA algorithm) using 4–6 arcs with 6MV x- rays.The gross tumor volume (GTV) was contoured using planning CT images. Planning target volume (PTV) margins were set at 5 mm; additionally, small spheres of 1 cm in diameter with separation of about 2 cm were created inside the GTV to deliver high dose LRT. DVHs of the vertices, critical structures and PTV were generated; plan quality and QA procedure were evaluated. Results: To quantify the dose oscillation between vertices has been calculated the "global conformity index" (0.9 6 CN 6 1). The 3D "peak to valley" dose all off characteristic is obtainable. Further more a good agreement (DD3%, DTA3 mm) between calculated and measured dose distribution has been obtained in 3DQA pretreatment procedure performed with Delta4 Phantom (Scandidos AB) to affirmdeliverability and accuracy of a RapidArc-based Lattice dose plan. Conclusions: Modern RT methods are available to deliver 3D High 1712 dose LRT; that for its bystander clinical effects can be used as induc- 1713 tion therapy followed by conventionally RT.